Thermal and flammability characteristics of blended jatropha bio-epoxy as matrix in carbon fiber–reinforced polymer - Mohd Radzi, Mohd Hafiezal; Abdan, Khalina; Zainal Abidin, Zurina; Md Deros, Mohd Azaman; Zin, Mohd Hanafee (MDPI, 2019)
This purpose of this paper was to reveal characteristics of a composite structure containing carbon fiber as a reinforcement and blended synthetic epoxy/bio-epoxy derived from crude jatropha oil as resin and compared with fully synthetic epoxy. The composite structure was prepared by the vacuum-assisted resin transfer molding technique and was left to cure for 24 h at room temperature. Both were characterized for their thermal, chemical, and flammable characteristics. The incorporation of jatropha bio-epoxy into the matrix significantly improved the thermal stability between 288–365 °C as obtained by thermogravimetric analysis (TGA) test. Dynamic mechanical analysis (DMA) curves showed slight diminution of performances and Tg from DMA tests confirmed well with the trend of Tg obtain by differential scanning calorimetry (DSC) curves. On the other hand, the flammability property was rated horizontal burning (HB) which was the same as the fully synthetic composite, but the duration to self-extinguish was halved for the composite with jatropha bio-epoxy. Fourier transform infrared attenuated total reflectance (FT-IR/ATR) was conducted to determine the difference of functional groups’ spectrum due to bonding type existing on both specimens. Overall, the composite specimen with blended bio-epoxy exhibited better thermal stability, comparable flammability characteristics, and performances. The aim of this paper was to introduce bio-based epoxy as a potential alternative epoxy and to compete with synthetic epoxy so as to minimize the footprint of non-renewable composite.